Non-invasive monitoring of goldenberry freezing using infrared thermography and radiofrequency dielectric spectroscopy. - Chuquizuta Trigoso, Tony Steven (2025)
This study presents a non-invasive monitoring system combining infrared thermography and radiofrequency dielectric spectroscopy to characterize the freezing behavior of goldenberry (Physalis peruviana). The system enabled simultaneous acquisition of surface temperature profiles, internal dielectric responses, and emissivity changes during freezing at − 40 ◦C. Thermal imaging revealed distinct freezing stages, including subcooling, ice nucleation, and vitrification, with emissivity decreasing to 0.837 during initial dehydration and increasing to 0.951 near the glass transition (− 35.8 ◦C). Emissivity variations revealed key thermal transitions, while dielectric measurements identified α- and β-dispersions linked to ionic straight and surface tension of ice Ih formation, with relaxation frequencies decreasing progressively as freezing advanced. The integration of both techniques allowed the detection of critical phase transitions, including the onset and completion of ice crystallization, supported by differential scanning calorimetry. These findings provide insight into structural changes and water mobility in high-moisture fruits, enabling real-time assessment of freezing kinetics. The approach demonstrates significant potential for optimizing industrial freezing protocols, improving the preservation of delicate fruits by minimizing structural damage and degradation of bioactive compounds.